2016
DOI: 10.1093/icvts/ivw211
|View full text |Cite
|
Sign up to set email alerts
|

Spread through air spaces is a predictive factor of recurrence and a prognostic factor in stage I lung adenocarcinoma

Abstract: Among stage I lung adenocarcinoma patients, spread through air spaces was found frequently in the invasive cases and was closely related to poor prognosis and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
153
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(174 citation statements)
references
References 24 publications
17
153
4
Order By: Relevance
“…More interestingly, the authors demonstrate that the presence of a micropapillary component together with STAS results in a shift of the T stage compared to the same tumors without both features being present. In a further validation study STAS was confirmed as an independent prognostic parameter in multivariate analysis for both overall and recurrence-free survival (11). In a series of 544 ADC with a validation cohort of 541 patients, those with ADCs 3 cm or smaller and STAS had worse recurrence-free and overall survival than those without STAS.…”
Section: Prognostic Impact Of Stasmentioning
confidence: 82%
See 2 more Smart Citations
“…More interestingly, the authors demonstrate that the presence of a micropapillary component together with STAS results in a shift of the T stage compared to the same tumors without both features being present. In a further validation study STAS was confirmed as an independent prognostic parameter in multivariate analysis for both overall and recurrence-free survival (11). In a series of 544 ADC with a validation cohort of 541 patients, those with ADCs 3 cm or smaller and STAS had worse recurrence-free and overall survival than those without STAS.…”
Section: Prognostic Impact Of Stasmentioning
confidence: 82%
“…Another recent study concerning STAS in a series of 318 stage I ADC confirmed and extended the yet available data. The authors found significant associations of STAS with the male sex, the median CEA level, smoking status, median maxSUV, solid nodules on computed tomography, p-stage, EGFR wild-type, lymphovascular invasion, and pleural invasion (11). In a series of 209 ADC where the authors aimed to quantify STAS there were statistically significant associations between higher STAS and solid predominant ADC, pleural invasion, lymphatic invasion, vascular invasion, and tumor size ≥10 mm (13).…”
Section: Correlation Of Stas With Clinicopathological Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, the initial study also suggested that STAS is a significant risk factor for locoregional and distant recurrence in patients who underwent limited resection, but not in those underwent lobectomy (4). Nevertheless, several recently published studies, including ours, have proved that the presence of STAS is closely related to reduced recurrencefree survival (RFS) and overall survival (OS) even in patients who underwent lobectomy (7,8). The largest case series consisting of more than 1,000 early stage ADCs (≤2 cm) has also confirmed that patients without STAS had better survival outcomes than those with STAS independent of resection type (lobectomy or limited resection) (9).…”
mentioning
confidence: 67%
“…The authors found significant associations of STAS with the male sex, the median CEA level, smoking status, median maxSUV, solid nodules on computed tomography, p-stage, EGFR wild-type, lymphovascular invasion, and pleural invasion (11). In the series by Uruga et al where STAS was semi-quantitatively analyzed in 208 stage I ADC there were statistically significant associations between higher STAS and solid predominant ADC, pleural invasion, lymphatic invasion, vascular invasion, and tumor size ≥10 mm (4).…”
mentioning
confidence: 95%